Pyridostigmine Improves the Effects of Resistance Exercise Training after Myocardial Infarction in Rats - Feriani, Daniele J.; Coelho-Júnior, Hélio J.; de Oliveira, Juliana C. M. F.; Delbin, Maria A.; Mostarda, Cristiano T.; Dourado, Paulo M. M.; Caperuto, Érico C.; Irigoyen, Maria C. C.; Rodrigues, Bruno (Frontiers in Physiology, 2018)
Myocardial infarction remains the leading cause of morbidity and mortality worldwide. Exercise training and pharmacological treatments are important strategies to minimize the deleterious effects of myocardial infarction. However, little is known about the effects of resistance training combined with pyridostigmine bromide (PYR) treatment on cardiac and autonomic function, as well as on the inflammatory profile after myocardial infarction (MI). Thus, in the present study, male Wistar rats were randomly assigned into: control (Cont); sedentary infarcted (Inf); PYR- treated sedentary infarcted rats (Inf+P); infarcted rats undergoing resistance exercise training (Inf+RT); and infarcted rats undergoing PYR treatment plus resistance training (Inf+RT+P). After 12 weeks of resistance training (15-20 climbs per session, with a 1-minute rest between each climb, at a low to moderate intensity, 5 days a week) and/or PYR treatment (0.14 mg/mL of drink water), hemodynamic function, autonomic modulation, and cytokine expressions were evaluated. We observed that 3 months of resistance training and PYR treatment, either alone or in combination with exercise, can improve the deleterious effects of MI on left ventricle dimensions and function, baroreflex sensitivity, and autonomic parameters, as well as systemic and tissue inflammatory profile. Furthermore, additional benefits in a maximal load test and anti-inflammatory state of skeletal muscle were found when resistance training was combined with PYR treatment. Thus, our findings suggest that the combination of resistance training and PYR may be a good therapeutic strategy since they promote additional benefits on skeletal muscle anti-inflammatory profile after myocardial infarction.